THE EXPERIENCE OF CIVIL ENGINEERING SPECIALISTS WITH HIGH QUALIFICATION AT BIALYSTOK UNIVERSITY OF TECHNOLOGY (Academic journal Industrial Machine Building Civil Engineering, 2018)
This article shows the learning process of students-engineers in Poland, disciplines which were learning and the projects which were submitted. It also describes what the elements university consists of – library, main departments: architectural, civil and environmental engineering, electrical engineering, computer science, mechanical engineering, management, forestry, amount of students and teachers. The article marks studying process features and courses and subjects content. The main principles of teaching were set out. They were provided with using of the shown information variety methods. Comparison of education processes in Ukraine and in Poland is highlighted in the article.
Keywords: Bialystok University of Technology; education; learning agreement, composite structures; concrete for special application; concrete structures; demolition; steel structures; structural mechanics; timber and masonry structures; foundations; matura